2016
DOI: 10.18632/oncotarget.13080
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as an emerging therapy target for ovarian carcinoma

Abstract: Autophagy is a conserved cellular self-digestion pathway for maintenance of homeostasis under basal and stressed conditions. Autophagy plays pivotal roles in the pathogenesis of many diseases, such as aging-related diseases, autoimmune diseases, cardiovascular diseases, and cancers. Of special note is that accumulating data suggest an intimate relationship between autophagy and ovarian carcinoma. Autophagy is well identified to act as either as a tumor-suppressor or as a tumor-promoter in ovarian carcinoma. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 101 publications
0
50
0
Order By: Relevance
“…Previously, the role of autophagy in cancer therapy has been proposed. It is now well accepted that in response to various chemotherapeutic drugs, radiation, and targeted therapeutics, cancer cells show large‐scale accumulation of autophagic vacuoles . It has been reported that TAM induces autophagy in tumor cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the role of autophagy in cancer therapy has been proposed. It is now well accepted that in response to various chemotherapeutic drugs, radiation, and targeted therapeutics, cancer cells show large‐scale accumulation of autophagic vacuoles . It has been reported that TAM induces autophagy in tumor cells .…”
Section: Discussionmentioning
confidence: 99%
“…It is now well accepted that in response to various chemotherapeutic drugs, radiation, and targeted therapeutics, cancer cells show large-scale accumulation of autophagic vacuoles. [39][40][41] It has been reported that TAM induces autophagy in tumor cells. 26,42 Herein, Figure 3 showed that TAM increased autolysosome and the ratio of LC3II/LC3I mainly in U87 cells while potently inducing apoptosis in U251 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, autophagy is a target process in the therapy of cancer 159 and of ovarian cancer in particular. 160 With increasing recognition of the role of CAFs in carcinogenesis and progression, it is believed that targeting the metabolic cross-talk between epithelial cancer cells and CAFs could open novel therapeutic strategies to fight ovarian cancer. 161 Potential therapeutic strategies presently under investigation include, among others, inhibitors of the signaling pathways triggered by TGF-and HIF-1 , two known inducers of autophagy in CAFs (Fig.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…In this case, promoting autophagy can inhibit the progression of ovarian cancer. Autophagy induction is closely related to the promotion of apoptosis and inhibition of proliferation in ovarian cancer [11].…”
Section: Introductionmentioning
confidence: 99%